The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/hipo.20584
|View full text |Cite
|
Sign up to set email alerts
|

Distinct α subunits of the GABAA receptor are responsible for early hippocampal silent neuron‐related activities

Abstract: The modulatory actions of GABA(A) receptor subunits are crucial for morphological and transcriptional neuronal activities. In this study, growth of hamster hippocampal neurons on biohybrid membrane substrates allowed us to show for the first time that the two major GABA(A) alpha receptor subunits (alpha(2,5)) are capable of early neuronal shaping plus expression differences of some of the main neuronal cytoskeletal factors (GAP-43, the neurotrophin--BDNF) and of Gluergic subtypes. In a first case the inverse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…This is based on two pieces of evidence. (1) BDNF expression and release from target neurons depends on GABAergic depolarization in the first 2 weeks in vitro , whereas GABAergic activity reduces the synthesis of BDNF mRNA in mature neurons (Berninger et al, 1995; Marty et al, 1996; Vicario-Abejon et al, 1998; Giusi et al, 2009). (2) BDNF signaling deprivation leads to dendrite growth impairment in newborn neurons during development and in the adult (McAllister et al, 1996; Berghuis et al, 2006; Chen et al, 2006; Takemoto-Kimura et al, 2007; Bergami et al, 2008; Chan et al, 2008; Ageta-Ishihara et al, 2009; Suh et al, 2009).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…This is based on two pieces of evidence. (1) BDNF expression and release from target neurons depends on GABAergic depolarization in the first 2 weeks in vitro , whereas GABAergic activity reduces the synthesis of BDNF mRNA in mature neurons (Berninger et al, 1995; Marty et al, 1996; Vicario-Abejon et al, 1998; Giusi et al, 2009). (2) BDNF signaling deprivation leads to dendrite growth impairment in newborn neurons during development and in the adult (McAllister et al, 1996; Berghuis et al, 2006; Chen et al, 2006; Takemoto-Kimura et al, 2007; Bergami et al, 2008; Chan et al, 2008; Ageta-Ishihara et al, 2009; Suh et al, 2009).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Notably, application of muscimol reduced the number of primary dendrites when applied 2 weeks after plating (after the excitatory to inhibitory switch of GABA responses takes place), again suggesting the requirement of depolarizing GABA. Interestingly, in a recent paper, a possible involvement of the α5 subunit (but not β2) of the GABA A receptor was suggested for the GABA-induced effect on neurite outgrowth via lowering of brain-derived neurotrophic factor (BDNF) levels in hamster hippocampal neurons treated with a specific α5 inverse agonist (Giusi et al, 2009). The latter results, again, point to a possible involvement of tonic GABA signaling in neuritogenesis.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study investigates the protective effect of didymin against H 2 O 2 -induced damage to the neuronal cells in a biohybrid membrane system model. Previous studies have demonstrated that semipermeable polymeric membranes in flat and hollow fiber configurations, thanks to their highly selective structural, physicochemical and transport properties, allow the successful in vitro reconstruction of neuronal tissue, reproducing a tissue model for studying metabolic diseases and drug effects [Woerly et al, 1996;Schmidt and Leach, 2003;Zhang et al, 2005;De Bartolo et al, 2008;Giusi et al, 2009;He et al, 2009;Morelli et al, 2010;Di Vito et al, 2011;Morelli et al, 2012b, c]. It was recently reported that polycaprolactone (PCL)-based membranes successfully supported outgrowth and differentiation of human neuronal cells [Morelli et al, 2012a].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed during the arousal state, the switching ON of α 1 may lead to a structurally well-assembled GABA A R complex [29] and consequently the activation of motor-controlling neurogenic programs in order to face new functional plasticity states [30]. Moreover, the predominance of a α 1 -dependent pharmacological organizational and functional features [8] have already been reflected during the early neuronal developmental stages of another major limbic region in hamsters and precisely the hippocampus [31] as well as on the induction of visual functions in other adult rodents [32]. As a consequence, it might very well be that the high levels of hypothalamic α 1 -containing neurons may assure a pharmacological protective role against ischemic insults during the awakening phase [19,33] especially since an increased gene expression of this subunit has been correlated to the new functional plasticity states during the arousal phase [34].…”
Section: Discussionmentioning
confidence: 99%